PERAN NILAI BUDAYA MADURA DALAM PEMBELAJARAN MENYIMAK DAN MENCERITAKAN KEMBALI: SEBUAH PENDEKATAN ETNOSAINS DI SDN PARSANGA II - Muhammad Romli; Ketut Suma; I Wayan Suastra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the role of Madurese cultural values in listening and retelling activities at the elementary school level through an ethnoscience approach. This approach is based on the assumption that local culture can serve as a contextual learning source to enhance students’ oral literacy while instilling character values and cultural identity. The study was conducted at SDN Parsanga II, Sumenep Regency, using a descriptive qualitative method. The research subjects consisted of 10 fourth-grade students selected purposively for interviews. Data collection techniques included semi-structured interviews, classroom observations, and documentation. The findings reveal that local stories such as karapan sapi, the legend of Roro Kuning, and fishermen’s narratives are closely related to students lived experiences, enabling them to understand and retell the stories more effectively. Students also demonstrated positive emotional responses such as enjoyment, confidence, and pride when engaging with culturally relevant content. These results align with contextual learning theory and ethnopedagogical perspectives, reinforcing prior research on the effectiveness of ethnoscience in language learning. Integrating Madurese cultural values has proven to enhance listening and storytelling skills while promoting cultural identity and the preservation of local traditions. The study recommends that teachers and education policymakers develop contextual, culturally based learning materials suitable for primary education.